Sustainable negative emissions in Europe: evaluating scenarios to meet carbon neutrality by 2050 - Johanna Markkanen; Kati Koponen; Antti Lehtilä (Environmental Research Letters, 2024)
Using the Pan-European TIMES-VTT model, we studied pathways for carbon neutrality by 2050 for 31 European countries by modelling a large portfolio of various terrestrial and technological carbon dioxide removal (CDR) strategies. Negative emission technologies and practices (NETPs) such as af-/reforestation, soil carbon sequestration, bioenergy with carbon capture and storage, direct air capture and storage, biochar, and enhanced weathering were considered. Three different storylines were created to describe the role of NETPs in varying future developments. The scenario storylines illustrate potential opportunities and constraints for large scale NETP implementation focusing on (1) optimistic technology development, (2) strict protection of planetary boundaries, and (3) increased self-sufficiency due to geopolitical risks associated with policy fragmentation. The results show that the demand for NETPs could be on a gigaton scale to reach carbon neutrality in Europe by 2050. As different countries have different opportunities to implement NETPs, none of the NETP options should be excluded from mitigation portfolios at this stage. The results also indicate the potential of NETPs in providing cost-effective solutions for achieving climate targets. On the other hand, stricter greenhouse gas emission reduction policies are needed to avoid over-reliance on CDR.